CAUSES AND EFFORTS TO REDUCE ANXIETY IN STROKE PATIENTS - Amalia, Nanda Kurnia; Harianto, Susilo; Muhalla, Hafna Ilmy (Universitas Airlangga, 2022)
Introduction: Stroke can cause mild to severe disability, which is the main trigger for anxiety and other effects of stroke. The purpose of this study was to describe some things of the anxiety of stroke patients at RSUD Ibnu Sina Gresik. Methods: This study used a descriptive research design. The population were stroke patients at RSUD Ibnu Sina Gresik in March 2022. The sample in this study was 78 respondents using the purposive sampling technique. The instrument used is a HARS scale questionnaire, analyzed by descriptive method and presented using a distributive table. Results: As many as 87.2% of respondents experienced anxiety. Most of the respondents had a mild level of anxiety (51.3%). It happened because most respondents were outpatients who had entered the recovery period. The most common cause of anxiety among respondents was illness (80.8%) and decreased work productivity (29.5%). The most efforts made by respondents to reduce anxiety were by worshipping and praying (64.1%) and telling stories to trusted people (62.8%). Nurses have an essential role in reducing the anxiety of stroke patients. Conclusions: Most stroke patients at RSUD Ibnu Sina Gresik experienced mild anxiety caused by illness and decreased work productivity. Most efforts are made to reduce anxiety, namely by worshipping and praying and telling stories to trusted people.